Bibliometric Analysis of Bioactive Agents for Anemia Treathment: Trends and Opportunities - Febriana, Ardelia; Yuniarti, Elsa (Jurnal Biologi Tropis, 2025)
Anemia is a global health problem affecting approximately 1.62 billion people, mainly in developing countries. Although iron supplementation is the main strategy, the use of biological agents as an alternative to traditional medicine has potential that has not been fully explored. This study aims to map the research landscape of biological agents as anti-anemia using bibliometric analysis. The study used a library research method by analyzing metadata from Scopus indexed articles for the period 2000-2024 using keywords related to anemia and traditional medicine. Data were analyzed using VOSViewer software to visualize the network and relationships between article citations. The analysis showed 208 relevant documents, with a significant increase in publications after 2010. China dominated with 55 publications, followed by India with 40 publications. The VOSViewer visualization identified three main clusters grouping different plant species, with some plants such as Curcuma longa, Aloe vera, and Hibiscus sabdariffa frequently associated with the treatment of anemia. The analysis also revealed many unexplored areas of research, especially in plant species that have not been commonly studied. This study concludes that of the more than 200 plant species with anti-anemia potential, many have not been comprehensively studied, opening up opportunities for further research especially in countries with high biodiversity such as Indonesia.